A method for preliminary seismic design and assessment of low-rise structures protected with buckling-restrained braces. (15th September 2016) - Guerrero, Hector; Ji, Tianjian; Teran-Gilmore, Amador; Escobar, J. Alberto
Highlights: A method for Performance-Based Seismic Design (PBSD) of low-rise structures with BRBs is proposed. The method assumes that structures equipped with BRBs behave as dual systems. It generates information useful for preliminary performance assessment of the structure. Therefore, it allows the rapid application of PBSD philosophy in low-rise buildings. An example of application is provided to show the applicability of the proposed method. Abstract: This paper proposes a method for preliminary Performance-Based Seismic Design (PBSD) of low-rise structures protected with Buckling-Restrained Braces (BRBs). It is assumed that a frame structure protected with BRBs, termed as a dual structure, is rationally represented by a dual single-degree-of-freedom (SDOF) oscillator whose parts yield at different displacement levels. The formulation of the method is presented for SDOF structures. This simplification is validated using a case study example. A comparison of the responses between conventional and dual structures shows that, when designing dual structures, the common practice of using conventional design spectra may lead to biased designs. One of the main advantages of the method is that, during its application, information useful for preliminary and quick assessment of structures is generated, facilitating the application of the PBSD philosophy. A case study example is conducted to show its applicability and its potential for preliminary assessment of structures. Regarding its limitations, the method is valid for low-rise regular buildings with rigid in-plane diaphragms, and whose dynamic response is dominated by their fundamental mode of vibration.